1993
DOI: 10.1038/366351a0
|View full text |Cite
|
Sign up to set email alerts
|

GTP binding and hydrolysis by the signal recognition particle during initiation of protein translocation

Abstract: The signal recognition particle (SRP) consists of one RNA and six protein subunits. The N-terminal domain of the 54K subunit contains a putative GTP-binding site, whereas the C-terminal domain binds signal sequences and SRP RNA. Binding of SRP to the signal sequence as it emerges from the ribosome creates a cytosolic targeting complex containing the nascent polypeptide chain, the translating ribosome, and SRP. This complex is directed to the endoplasmic reticulum membrane as a result of its interaction with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
168
1
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 30 publications
10
168
1
1
Order By: Relevance
“…In early work, we also showed that synthetic peptides corresponding to functional signal sequences modulate the GTPase activity of SRP/SRP receptor, while nonfunctional peptides do not. 30 Subsequent experiments in our lab 31 brought these results into question because of artifactual interactions between the signal peptides and the RNA SRP component; nonetheless, this research study paved the way for our ongoing studies of SRP-signal peptide interaction (see later).…”
Section: Signal Peptide Conformations and Membrane Interactionsmentioning
confidence: 99%
“…In early work, we also showed that synthetic peptides corresponding to functional signal sequences modulate the GTPase activity of SRP/SRP receptor, while nonfunctional peptides do not. 30 Subsequent experiments in our lab 31 brought these results into question because of artifactual interactions between the signal peptides and the RNA SRP component; nonetheless, this research study paved the way for our ongoing studies of SRP-signal peptide interaction (see later).…”
Section: Signal Peptide Conformations and Membrane Interactionsmentioning
confidence: 99%
“…Its features are very similar to those of the 54-kDa subunit of mammalian SRP (SRP54), which consists of structurally distinct, N-terminal G-and C-terminal M-domains (Bernstein et al, 1989;Romish et al, 1989). The G-domain contains three GTP-binding motifs and it may play an essential role mediating the interaction between SRP and SRP receptor (Miller et al, 1993). The M-domain is characterized by a high content of methionine residues.…”
mentioning
confidence: 99%
“…The G domains of SRP54 and SR␣ define a distinct subfamily within the Ras-like G proteins (20), the SRP GTPases, which are structurally characterized by an insertion (I-box) in the effector region and a close interaction with the N domain (21, 22). The GTPases in both SRP54 and SR␣ stimulate each other upon complex formation and have been proposed to act as GTPase-activating proteins for each other (8,9).SRP function relies on the tightly controlled communication of SRP54 with external regulators (e.g., the ribosome, the SR, and the translocon) and on internal communication between the domains of SRP54. For example, the interaction of SRP with the ribosome increases the affinity of SRP54 for GTP (23).…”
mentioning
confidence: 99%